The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5cp04977f
|View full text |Cite
|
Sign up to set email alerts
|

High resolution absolute absorption cross sections of the B̃1A′–X̃1A′ transition of the CH2OO biradical

Abstract: Carbonyl oxides, or Criegee intermediates, are formed from the gas phase ozonolysis of alkenes and play a pivotal role in night-time and urban area atmospheric chemistry. Significant discrepancies exist among measurements of the strong B ̃(1)A'-X ̃(1)A' electronic transition of the simplest Criegee intermediate, CH2OO in the visible/near-UV. We report room temperature spectra of the B ̃(1)A'-X ̃(1)A' electronic absorption band of CH2OO acquired at higher resolution using both single-pass broadband absorption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
80
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(92 citation statements)
references
References 42 publications
10
80
1
Order By: Relevance
“…The UV spectra of CH 2 OO under bulk conditions were later reported by three groups: Sheps 27 using cavity-enhanced absorption spectroscopy, Ting et al 25 using single-pass absorption spectroscopy, and Foreman et al 28 using single-pass absorption and cavity ring-down spectroscopy. Utilizing the fact that SO 2 reacts quickly with CH 2 OO, Ting et al 25 obtained a reliable UV absorption spectrum of CH 2 OO, which is consistent with later reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV spectra of CH 2 OO under bulk conditions were later reported by three groups: Sheps 27 using cavity-enhanced absorption spectroscopy, Ting et al 25 using single-pass absorption spectroscopy, and Foreman et al 28 using single-pass absorption and cavity ring-down spectroscopy. Utilizing the fact that SO 2 reacts quickly with CH 2 OO, Ting et al 25 obtained a reliable UV absorption spectrum of CH 2 OO, which is consistent with later reports.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,12,13 CH 2 OO is the simplest CI, and is therefore the prototypical CI for elucidating important issues of reactivity and structure. Spectroscopic characterizations of CH 2 OO have been carried out extensively in the vacuum ultraviolet (VUV), 2,24 ultraviolet (UV), [25][26][27][28] infrared, 29-31 microwave [32][33][34][35] and terahertz 32 regions. Taatjes et al 2,24 reported the first direct identification of CH 2 OO by employing VUV photoionization mass spectroscopy, which can detect selectively ionized CH 2 OO instead of its more stable isomers.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Pulsed laser photolysis of CH2I2 at 355 nm generated CH2I radicals, which reacted rapidly with O2 to produce CH2OO in high yield. [32][33][34][35][36] Transient absorption spectroscopy using broadband pulsed LEDs was used to measure the time-dependent concentration of CH2OO in the absence and presence of a controlled concentration of acid.…”
mentioning
confidence: 99%
“…The LED output spanned the wavelength range 365-388 nm, capturing several characteristic vibronic bands of the CH2OO B̃-5 X̃ transition. [31,37,38] Selectivity is important because secondary chemistry results in formation of IO, [35,39] which absorbs in the same spectral window. Typical transient spectra obtained at several time delays in the absence of acid are shown in Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation